Henrik Ibsen. Drammatis Personae Between Reality and Fiction - Gokaj, Rregjina; Turku, Marsela (Mediterranean Journal of Social Sciences, 2012)
Literature is a powerful way of transmitting ideas and attitudes thus intercultural communication comes through authors’ ideasand readers’ assumptions. This article will be focussed in some major dramas of Henrik Ibsen, as one of the most powerfulrepresentatives of European drama of the late nineteenth century. His contribution to the modern thought is, without doubt, vital andprecious especially in Pillars of Society, A Doll’s House, Ghosts, Hedda Gabler etc. This article is going to browse some of Ibsen’s playsconsidering the usage he makes of symbols and symbolism, reality and realism. ‘A Doll’s House’ is considered a landmark in thedevelopment of what soon became a highly prevalent genre of theatre – realism, which strives to portray life accurately and shunsidealized visions of it. Thus Ibsen presents us to Nora and Helmer who are the antitypes of Mr. and Mrs. Alving of ‘Ghosts’. If weconsider ‘Ghosts’, which followed ‘A Doll’s House’ not only consequently but even in the realistic and innovative mode of writing, the ideaof marriage is quite a useless sacrifice of human beings who do not have the same interests or principles in life. Some of these featuresmay also be seen in The Lady from the Sea with Ellida and Wangel and their relationship. These aspects and others of Henrik Ibsen’splays will be the focus of this paper, showing the playwright’s contribution to World Literature.